2010
DOI: 10.1021/bm1001203
|View full text |Cite
|
Sign up to set email alerts
|

Stress-Transfer in Anisotropic and Environmentally Adaptive Cellulose Whisker Nanocomposites

Abstract: Quantitative insights into the stress-transfer mechanisms that determine the mechanical properties of tunicate cellulose whisker/poly(vinyl acetate) nanocomposites were gained by Raman spectroscopy. The extent of stresstransfer is influenced by local orientation (or anisotropy) of the whiskers, which in turn is governed by the processing conditions used to fabricate the nanocomposites. Solution-cast materials display no microscopic anisotropy, while samples that were cast and subsequently compression molded co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 102 publications
(101 citation statements)
references
References 31 publications
7
94
0
Order By: Relevance
“…It was noted that the shift in this band is higher in magnitude for dry networks compared to wet samples, in agreement with previous work on wet cellulose nanowhisker-based composite materials 38 . Figure 8a reports the detailed positions of the Raman band initially located at 1095 cm -1 as a function of strain for dry unmodified and glyoxalized BC networks.…”
Section: Resultssupporting
confidence: 91%
“…It was noted that the shift in this band is higher in magnitude for dry networks compared to wet samples, in agreement with previous work on wet cellulose nanowhisker-based composite materials 38 . Figure 8a reports the detailed positions of the Raman band initially located at 1095 cm -1 as a function of strain for dry unmodified and glyoxalized BC networks.…”
Section: Resultssupporting
confidence: 91%
“…Quantitative insights into the stress-transfer mechanisms that determine the fi lms stiffness were gained by Raman spectroscopy. 90 A diagnostic Raman band, associated with the C-O ring stretching of the cellulose backbone, was used to quantify the local orientation of and the level of stress experienced by the cellulose whiskers. It was shown that the extent of stress-transfer is infl uenced by local orientation and connectivity of the cellulose whiskers; these features are governed by the processing conditions used to fabricate the materials.…”
Section: Innovation Through Bioinspirationmentioning
confidence: 99%
“…The fixed mechanical properties of typical materials used in micromachined Si, polyimide, or parylene neural probes cannot be optimized for both brain penetration and long-term deployment. Thus PVAc-TW, and the new class of mechanically adaptive polymer nanocomposites that it represents [8,25,26], provides a potential advantage over conventional polymers for penetrating probe-based neural interfacing in that the nanocomposite is sufficiently rigid for probe insertion, but upon deployment absorbs biological fluids, becoming much more pliable to better mechanically match brain tissue. Fabrication of neural probes from such polymers will enable researchers to evaluate the role that mechanics plays in long-term neural recording.…”
Section: Introductionmentioning
confidence: 99%